2014
DOI: 10.1111/jhn.12274
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intake among US adults with disabilities

Abstract: Interventions targeting persons with disabilities through nutrition education and financial assistance are warranted to promote healthy diet and reduce disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…A comparison of our data with that of a general population showed that our subjects had a lower intake of most micronutrients (9,42) , even in comparison with institutionalised elderly (41,45) .These results are consistent with another study showing that individuals with disabilities are less likely to meet the RDA in comparison with individuals without disabilities (46) . Our results for low folate and vitamin D intakes are consistent with other studies in general populations (8,47) .…”
Section: Discussionsupporting
confidence: 89%
“…A comparison of our data with that of a general population showed that our subjects had a lower intake of most micronutrients (9,42) , even in comparison with institutionalised elderly (41,45) .These results are consistent with another study showing that individuals with disabilities are less likely to meet the RDA in comparison with individuals without disabilities (46) . Our results for low folate and vitamin D intakes are consistent with other studies in general populations (8,47) .…”
Section: Discussionsupporting
confidence: 89%
“…However, among adults with disabilities, overall dietary intake is not well understood and the intake of foods or beverages that may contribute to poor diet quality, such as SSBs, is not documented. According to 2007–2010 NHANES data (18), the amount of saturated fat intake was likely to exceed the recommended daily limit among adults with disabilities, whereas the amount of fiber, vitamin A, vitamin C, calcium, and potassium intake was less likely to meet recommendations. Using 2011 BRFSS data, one study found that adults with disabilities consumed fruits and vegetables less frequently than adults without disabilities (22).…”
Section: Discussionmentioning
confidence: 99%
“…Although general information on dietary intake among adults with disabilities is available (18), no details are available on the association between disability status and SSB consumption. To the best of our knowledge, our study is the first to investigate this topic.…”
Section: Introductionmentioning
confidence: 99%
“…1e3 Based on data from the National Health and Nutrition Examination Survey (NHANES) 2007e2008 and 2009e2010 waves, over a quarter of U.S. adults had one or more self-reported functional limitations. 4 Increasing evidence suggests people with obesity are at higher risk for functional limitations, especially those related to mobility. 5,6 In addition to the associated chronic illnesses including type 2 diabetes mellitus, hypertension, dyslipidemia, heart disease, and certain types of cancer, 7 obesity may directly influence physical functions through its detrimental impact on lower limb muscular strength and power, plantar foot pressure, inflammatory milieu, sarcopenia, and knee osteoarthritis.…”
mentioning
confidence: 99%